2012 US SoFA Launch "Investing in Agriculture for a Better Future" - Wiebe, Keith (2013)
US Launch of The State of Food and Agriculture 2012 "Investing in Agriculture for a Better Future" presentation at IFPRI on 22 January 2013 by Keith Wiebe, Food and Agriculture Organziation of the United Nations.